Government security types and their modeling - Deacon, Mark (Henry Stewart Talks, 2009)
What are government securities?, Fixed rate bonds, Inflation indexed bonds, Floating rates bonds, Other types of bonds, Accrued interest, How should an investor value a bond?, Using redemption yields, Duration, Price/yield relationship, Yield curve modeling, Which bonds should be used to estimate yield curve?, Uses of the yield curve